Convictions Beyond the Bomb: Interplays Between Violence, Religion and Development in Sri Lanka (abstract) - Indika Bulankulame (Revue Internationale de Politique de Développement)
Prior to the conclusion of 30 years of civil war, many ordinary Sri Lankans were caught in bombings intended to disrupt daily life. This occurred not only in the war zone, but also in urban areas, primarily the capital of Colombo. While many lost their lives, others survived – scarred, disabled and traumatised. This chapter explores the meaning of ‘survival’ as experienced in newly-formed role of ‘bomb victim’. In doing so, this chapter questions the capacity of survivors to be productive as breadwinners and/or deal with the severe economic dislocations resulting from the drastic changes in their lives’ trajectories. Overall, the chapter finds that the loss of income and inability to fully participate in the market economy isolating the survivors from the main discourses of development, and purported opportunities offered therein. The end of hostilities has marked a clear drive to develop Sri Lanka, and in this important post-war stage, it is important to note the various ways in which religion is used to address survival needs. This chapter thus highlights the dynamic interplay between religion, political violence and development. In doing so, the chapter examines religious responses to (neo) liberal, market-driven globalisation, the experience of terror and violence, and the interaction thereof.